Unveiling Neck Pain in Young Adults: A Descriptive Study Using Magnetic Resonance Imaging of Cervical Spine Highlighting Poor Posture and Degenerative Disc Disease - Nitesh Narendra Agarwal; Pankaj Asaram Badarkhe; Sahebrao Bhumanna Kaslod; Meenakshi Induprakash Gajbhiye (International Journal of Anatomy Radiology and Surgery, 2025)
Introduction: Neck pain is a widespread issue among the elderly, often causing disability and affecting daily activities. Recently, there has been an alarming rise in neck pain among young adults. Aim: To assess the causes of neck pain in symptomatic young adults (ages 11-35 years) and identify modifiable risk factors. Materials and Methods: An observational descriptive study was conducted in the Department of Radiodiagnosis of Government Medical College, Akola, Maharashtra, India from October 2023 to June 2024. A set of predefined questions was used to collect data on clinical symptoms, socio-demographic information and factors associated with neck pain. Magnetic Resonance Imaging (MRI) of the cervical spine was performed using a 1.5 Tesla Philips Ingenia system. Structural pathologies in the cervical spine and cervical spinal cord, like degenerative changes and congenital/developmental anomalies with their associated findings, were noted. Descriptive statistics was used and results were expressed in terms of frequency and percentage. Results: Out of the 50 participants, 32 were males and 18 were females, with mean age of 27 years. Abnormal MRI findings were identified in 18 males (56.25%) and 10 females (55.56%). The leading cause among the abnormal findings was degenerative disc disease, with 18 cases (64.29%), followed by congenital and developmental factors-6 cases (21.43%), trauma-3 cases (10.71%) and inflammatory conditions-1 case (3.57%). Among the 18 cases of disc degeneration, 14 (77.78%) were involved in prolonged sedentary behaviour (more than eight hours per day), while 4 (22.22%) were engaged in an active lifestyle. Additionally, 9 cases (50%) reported more than four hours of daily mobile or computer use, whereas only 3 cases (16.67%) reported less than two hours of daily use. Conclusion: There is a strong link between neck pain, prolonged sedentary behaviour and extensive mobile or computer use.